The Impact of Gender Inequality and Good Governance on Health Status: Evidence from Upper-middle-income Countries - Mahdi Shahraki; Mojtaba Abbasian; Mehdi Safdari (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: Gender equality and good governance are the most important social indicators affecting health status and well-being. Therefore, the present study aimed to investigate the impact of gender inequality and good governance on health status in upper-middle-income countries. Methods: The present ecological and applied study was conducted on upper-middle-income countries using the cross-sectional data method and the Common Correlated Effect Means Group estimator by STATA software (version 16). A total of 33 upper-middle-income countries were selected non-randomly. Data for 2000-2019 were extracted from the databases of the World Bank and the United Nations. Results: The mean of life expectancy index, under-five mortality rate, gender inequality index and good governance were 71.25, 25.28, 0.42 and -1.26. The impact of gender inequality index, good governance index, health expenditures and women's participation rate on life expectancy were equal to -1.15, 0.031, 0.040 and 0.009, respectively, and impact of gender inequality index and per capita GDP on the infant mortality rate were 12.062 and -5.183, respectively. Conclusion: Gender inequality index had a negative effect and good governance, health expenditures and women's participation rate in the labor market had a positive effect on life expectancy; Gender inequality index also had a positive effect and per capita GDP had a negative effect on child mortality rate. Therefore, policies to reduce gender inequality, such as improving women's education, increasing women's participation in parliament, and increasing women's employment are proposed.